Pemeriksaan Kesehatan Glukosa Darah Sewaktu dan Tekanan Darah serta Pemasangan Media Edukasi di Samsat Kabupaten Pandeglang - Ucu Wandi Somantri; Ika Purwanto; Dinah Febriyanti; Nurul Aziza; Nur Kholisyah; Sigit M Ramdian (Universitas 45 Surabaya, 2025)
The health check-up of blood glucose and blood pressure, as well as the installation of health education media at Samsat Pandeglang Regency, aims to increase public awareness of the importance of routine health monitoring. This activity was attended by 35 participants, consisting of residents who visited Samsat for vehicle administration purposes. Blood glucose tests are used to measure blood glucose levels and monitor potential diabetes risk, while blood pressure tests aim to detect symptoms of hypertension. Both of these tests are important in the prevention of non-communicable diseases that often go undetected in the early stages. In addition to health checks, the installation of educational media in the form of posters, brochures, and leaflets is carried out in strategic locations within Samsat to disseminate information related to healthy lifestyles, diabetes management, hypertension prevention, and the importance of routine checkups. This educational media aims to provide information that is easy to understand and accessible to the public to increase their understanding of how to maintain health independently. The results of this activity show that health checks provide direct benefits for participants in knowing their health conditions, while educational media have succeeded in increasing public awareness of the importance of maintaining health and living a healthy lifestyle. It is hoped that this activity can encourage the community to be more concerned about their health.